"Normal" liver stiffness measure (LSM) values are higher in both lean and obese individuals: A population-based study from a developing country - Das, Kausik; Sarkar, Rajib; Ahmed, Sk. Mahiuddin; Mridha, Asit R.; Mukherjee, Partha S.; Das, Kshaunish; Dhali, Gopal K.; Santra, Amal; Chowdhury, Abhijit (Hepatology (Baltimore, Md.), 2012)
The liver stiffness measure (LSM) needs to be explored in ethnically and anthropometrically diverse healthy subjects (to derive an acceptable normal range) and also in patients with liver disease. In view of this objective, LSM was performed by transient elastography (TE) using FibroScan in 437 healthy subjects with normal alanine aminotransferase (ALT) levels, recruited from a free‐living population of the Birbhum Population Project (BIRPOP; www.shds.in), a Health and Demographic Surveillance System (HDSS), and from 274 patients with liver disease attending the Hepatology Clinic of the School of Digestive and Liver Diseases (SDLD; Institute of Post Graduate Medical Education & Research [IPGME&R], Kolkata, India) including 188 with nonalcoholic fatty liver disease (NAFLD) and 86 with chronic hepatitis of viral and other etiologies. Liver biopsy was performed in 125 patients. The range of normal values for LSM, defined by 5th and 95th percentile values in healthy subjects, was 3.2 and 8.5 kPa, respectively. Healthy subjects with a lower body mass index (BMI; < <18.5 kg/m2) had a higher LSM compared with subjects who had a normal BMI; this LSM value was comparable to that of obese subjects (6.05 ± 1.78 versus 5.51 ± 1.59 and 6.60 ± 1.21, P = 0.016 and 0.349, respectively). Liver disease patients without histologic fibrosis had significantly higher LSM values compared with healthy subjects (7.52 ± 5.49 versus 5.63 ± 1.64, P < 0.001). Among the histologic variables, stage of fibrosis was the only predictor for LSM. LSM did not correlate with inflammatory activity and ALT in both NAFLD and chronic hepatitis groups. Conclusion: LSM varies between 3.2 and 8.5 kPa in healthy subjects of South Asian origin. Both lean and obese healthy subjects have higher LSM values compared with subjects with normal BMI. Liver stiffness begins to increase even before fibrosis appears in patients with liver disease. (Hepatology 2012)